Evaluation of Ferric Ion Adsorption On The Surface Imprinting Adsorbent - Ihsan Alfikro; Jorena Jorena; Erry Koriyanti; Octavianus Cakra Satya; Fiber Monado; Idha Royani (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2024)
Rapidity in technological aspects encourages industrial sector to utilize and apply the latest technology to accelerate and optimize production in its field. Thus, waste from industry polluting various aspects of environment, such as water, gives rise to environmental impacts. Heavy metals, including iron, are one of the most common and dangerous pollutants often found in water environments. Therefore, consideration of methods for heavy metal separation from water becomes important. The adsorption method has been used for separating heavy metals because of its simplicity, thus effectively cuts energy consumption and costs in process. However, heavy metal characteristics in water can vary depending on the element. Consequently, understanding the heavy metal characteristics in water is important, hence capable of formulate appropriate and effective adsorption systems. This study, Fe(III)-IIPs was applied to adsorb and separate iron from water through repeated adsorption with parameter improvements. The pH parameter plays an important role, with ion competition happens at pH <2 and the formation of iron hydroxide species at pH >4.5, which results in adsorption inhibition. The modeling of adsorption kinetic equation was found that the adsorption system carries chemisorption characteristics, with adsorption capacity of 11.15 mg/g and reaction rate constant of 19 min-1.